RELEVANSI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KECERDASAN EMOSIONAL SISWA SEKOLAH MENENGAH PERTAMA - Suprima Suprima (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2022)
Education is basically a medium to build the nation's next generation of higher quality, both in terms of intellectual intelligence and emotional intelligence. In Islam itself, education is not only held to provide an understanding of the teachings of the Islamic religion, but also to foster and develop individual character. However, based on previous research, it can be seen that the level of emotional intelligence of junior high school students in several schools in Indonesia is still at a low and moderate level. This indicates the need to re-evaluate the existing curriculum to see its relevance to the development of students' emotional intelligence. This research uses a qualitative approach with a literature study method and is then analyzed and presented through a descriptive analysis method. The results of this study indicate the relevance of the Islamic religious education curriculum that can develop emotional intelligence through 5 indicators, namely self awareness, self management, self motivation, social awareness, and relationship management. This shows the need for curriculum development that can further hone student relationship management as an indicator of emotional intelligence that has not been accommodated.